A SHARIA RETURN AS AN ALTERNATIVE INSTRUMENT FOR MONETARY POLICY - Ashief Hamam (Economic Journal of Emerging Markets, 2011)
Rapid development in Islamic financial industry has not been supported by sharia monetary policy instruments. This study looks at the possibility of sharia returns as the instrument. Using both error correction model and vector error correction model to estimate the data from 2002(1) to 2010(12), this paper finds that sharia return has the same effect as the interest rate in the demand for money. The shock effect of sharia return on broad money supply, Gross Domestic Product, and Consumer Price Index is greater than that of interest rate. In addition, these three variables are more quickly become stable following the shock of sharia return. Keywords: Sharia return, islamic financial system, vector error correction modelJEL classification numbers: E52, G15